Analysis of the Implementation of Policy on Equalizing Administrative Positions to Functional Positions in Central Government Agencies - Istyadi Insani; Hardi Warsono; Kismartini Kismartini; Retno Sunu Astuti (Universitas Medan Area, 2022)
Equalization of positions from administrative positions to functional positions is one form of implementation of the policy of simplifying the bureaucracy into two levels in government agencies in Indonesia. This problem occurs because the equalization of positions is carried out in a relatively short time without being preceded by an in-depth study. This condition has an impact on the career uncertainty of functional officials as a result of the equalization which has an impact on the decline in employee performance and organizational performance. This study aims to analyze the process of equalizing administrative positions to functional positions in order to formulate inputs for improving the implementation of these policies in the field. The research method uses a qualitative descriptive approach. Research informants determined the snowball with key people Central Government Officials and related functional officials. Data was collected through observation, in-depth interviews and literature study. Data analysis techniques with data reduction, presentation and conclusion. The validity of the data using a triangulation technique of sources and data. This theory uses the theory of policy implementation. The results of the study indicate that the equalization of administrative positions to functional positions in government agencies needs to pay attention to communication factors, resources, dispositions and bureaucratic structures. Recommendations are in the form of policy proposals to improve arrangements for equalizing administrative positions to functional positions.